2006
DOI: 10.1111/j.1399-3046.2006.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term protection against hepatitis B in pediatric liver recipients can be achieved effectively with vaccination after transplantation

Abstract: Liver recipients who have antibodies to hepatitis B core antigen (anti-HBc) or received an anti-HBc positive liver graft are at risk of acquiring de novo hepatitis B infection so a life long prophylaxis is required. A post-transplant vaccination against hepatitis B virus (HBV) can offer a better alternative than either hepatitis B hyperimmune globulin (HBIG) or lamivudine. This study investigated the course of anti-HBs titer after vaccination and analyzed the factors that influence the response. Between Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 23 publications
1
45
0
4
Order By: Relevance
“…Prospective studies have shown that both pre-transplant and post-transplant vaccination are effective in preventing de novo HBV infection, though additional doses of the vaccine may be required to induce an effective immune response [44,45] . Our current recommendation for patients with non-HBV related liver disease is to be immunized for HBV.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Prospective studies have shown that both pre-transplant and post-transplant vaccination are effective in preventing de novo HBV infection, though additional doses of the vaccine may be required to induce an effective immune response [44,45] . Our current recommendation for patients with non-HBV related liver disease is to be immunized for HBV.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Для отдельных групп пациентов c высокими рисками развития HBV-инфекции рекомендованный целевой уровень антител может быть выше: 100-250 МЕ/л [30], 100-500 МЕ/л [31,32], тогда как в некоторых исследова-ниях считается достаточным уровень более 10 МЕ/л [12,23], более 20 МЕ/л [33].…”
Section: вакцинация после трансплантации печениunclassified
“…В группе с хорошим ответом был сущест-венно выше уровень антител к HBs-антигену до трансплантации, то есть вакцинация до ТП важна не только для защиты во время операции и на ран-них сроках после трансплантации, но и для улуч-шения иммунного ответа после трансплантации. По результатам исследования были сформулирова-ны следующие рекомендации: все пациенты долж-ны получать бустерную вакцинацию до трансплан-тации вне зависимости от серологического статуса, вакцинация должна проводиться не менее чем через 12 месяцев после трансплантации и не менее чем через четыре месяца после отмены преднизолона, концентрация такролимуса должна быть минималь-но возможной в момент начала вакцинации (реко-мендуемый уровень ниже 5 нг/мл) [33]. Многие исследователи рекомендуют проведение бустерной вакцинации до трансплантации вне зависимости от уровня антител для получения лучшего иммунного ответа при последующих ревакцинациях [33][34][35][36][37].…”
Section: вакцинация после трансплантации печениunclassified
See 2 more Smart Citations